Comparison of 18F activity measurements at the VNIIM, NPL and the ENEA-INMRI using the SIRTI of the BIPM. (March 2016) - Michotte, C.; Nonis, M.; Alekseev, I.V.; Kharitonov, I.A.; Tereshchenko, E.E.; Zanevskiy, A.V.; Keightley, J.D.; Fenwick, A.; Ferreira, K.; Johansson, L.; Capogni, M.; Carconi, P.; et al.
Abstract: In 2014, the first three comparisons of activity measurements of 18 F were carried out at the VNIIM, NPL and the ENEA-INMRI using the BIPM's Transfer Instrument of the International Reference System. The transfer instrument and the NMIs primary measurement methods are briefly described. The degrees of equivalence with the key comparison reference value defined in the frame of the corresponding SIR comparison have been evaluated. World-wide consistency of activity measurements of 18 F is demonstrated. Highlights: The SIRTI for activity comparisons of short-lived radionuclides was extended to 18 F. The three first 18 F SIRTI comparisons took place at the VNIIM, NPL and the ENEA-INMRI. Relative uncertainties of the NMIs primary measurements ranged from 0.3% to 0.6%. Relative uncertainties of the SIRTI measurements ranged from 0.06% to 0.14%. The comparison results agree with the SIR KCRV within 1 or 2 standard uncertainties.